Monitoreo de la carga y la radiación solar para el diseño de un sistema fotovoltaico en la casa No 10 del barrio María de la ciudad de Latacunga. - Salazar Achig, Edgar Roberto (2015)
This research aims to determine the magnitude of the solar potential in the house No. 10 Maria neighborhood in the city of Latacunga comes from direct and diffuse radiation. The parameters to be considered during the design are solar radiation in watts per square meter (W / m ^ 2), the load power in watts per hour (W / h) and construction costs ($): In initial stages They collect solar radiation values and the power demand of energy using equipment like pyranometer APOGEE MP-200 and the load analyzer FLUKE 1735; the data will be compared with the minimum building standards for such systems. It was found that between 8:00 to 16:00 the value of 200 W / m ^ 2 is exceeded; observing the results is estimated that at noon the photovoltaic module will have the maximum conversion of solar energy into electrical energy on a 192.05% surpassing the minimum required by the system design. With the implementation of photovoltaic panels will be able to supply on average up to 100% of the energy demand of the load "average single-family home in the urban sector" within 8 hours of usable sunlight (08:00 am to 16: 00 pm), which will reduce the costs of billing by the utility and mean substantial savings for the family. Two alternatives were proposed first with an implementation cost of $ 1,350.00 photovoltaic system which has a monocrystalline solar panel ZYTECH 230, an inverter and the support structure, the second alternative has a cost of $ 2970 implementation, 00; The system includes two ZYTECH 230P monocrystalline solar panels, a charge controller, an inverter, a battery and the support structure, the main difference reducing pollution the environment in the first is 0,16 2 and the second of 0,32 2.